Guðbrandur Vigfússon as an editor of Old Norse-Icelandic literature - Jakubczyk, Radosław (Folia Scandinavica Posnaniensia, 2016)
Guðbrandur Vigfússon, an Icelander born in Galtardalur, Dalasýsla, was without doubt one of the most influential scholars of Old Norse studies of his day. His diplomatic edition of Flateyjarbók, his critical edition of Sturlunga saga, and his anthology An Icelandic Prose Reader are still of use to those without access to the relevant manuscripts. In this essay, I would like to survey his career (in Copenhagen and Oxford) as an editor of Old Norse Icelandic texts and the legacy that he has left to his successors in the field of Old Norse studies.